Building on the proposal by the EU-Commission for reforming the Stability and Growth Pact - Jasper Van Dijk; Florian Schuster; Philippa Sigl-Glöckner; Vinzenz Ziesemer (Dezernat Zukunft e.V., 2022)
In the following, we very briefly sketch out the reform proposal put forward by the EUCommission and make five suggestions on how this could be developed further. The annex contains two short papers covering (1) the EU methodology for computing debt sustainability and (2) expenditure rules in practice drawing on the Dutch experience.
Keywords: 330